IMPLEMENTASI SEKOLAH RESPONSIF GENDER DI SDN KEDUNGKENDO CANDI SIDOARJO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Gender inequality and stereotypes in basic education practices still have the potential to hinder the optimal development of students. This research is based on the concept of gender mainstreaming and inclusive education theory, which emphasizes the principles of social justice, equal participation, and the elimination of discrimination in the school environment. The purpose of this study is to describe the implementation of gender-responsive schools at SDN Kedungkendo Candi Sidoarjo and identify factors that support its sustainability. The study used a qualitative approach with a phenomenological design. Data were collected through semi-structured interviews, participant observation, and documentation studies with purposively selected principals. Data analysis was carried out through data reduction, presentation, and drawing conclusions using triangulation techniques to ensure validity. The results show that the value of gender equality has been internalized in the school culture, reflected in equal leadership opportunities, the division of tasks without stereotypes, active participation in learning and extracurricular activities, and the provision of facilities that support the comfort and safety of all students. In addition, the principal's leadership support, collaboration between teachers, and partnerships with parents and external parties are important factors in strengthening the consistency of the implementation of equality values. Although not yet fully implemented in specific written policies, ongoing practice shows that gender-responsive schools can be built through habituation, role models, and the collective commitment of school residents in creating a fair, safe, and inclusive learning environment.